The family as a unit of analysis: a challenge for nursing - G. Vivar, Cristina (Investigación y Educación en Enfermería, 2013)
The concept of the family as a unit of analysis is an area being investigated from different disciplines like nursing, medicine, or sociology. Its interest has been growing upon identifying vulnerable families like those with a loved one with dependency or those enduring a chronic process, who have a series of necessities that must be studied to be effectively addressed by healthcare teams. This matter was dealt with in depth during the 11th International Congress on Family Nursing held in June 2013 in Minneapolis (USA), congregating 433 participants from 27 countries.1